2014
DOI: 10.1155/2014/872470
|View full text |Cite
|
Sign up to set email alerts
|

A Reliable Method for Rhythm Analysis during Cardiopulmonary Resuscitation

Abstract: Interruptions in cardiopulmonary resuscitation (CPR) compromise defibrillation success. However, CPR must be interrupted to analyze the rhythm because although current methods for rhythm analysis during CPR have high sensitivity for shockable rhythms, the specificity for nonshockable rhythms is still too low. This paper introduces a new approach to rhythm analysis during CPR that combines two strategies: a state-of-the-art CPR artifact suppression filter and a shock advice algorithm (SAA) designed to optimally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 44 publications
3
48
0
Order By: Relevance
“…[21][22][23] Generally, the specificity of these methods is below the 95% value recommended by the AHA. 13 Furthermore, when used to continuously monitor the rhythm during CPR their performance degrades substantially.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] Generally, the specificity of these methods is below the 95% value recommended by the AHA. 13 Furthermore, when used to continuously monitor the rhythm during CPR their performance degrades substantially.…”
Section: Discussionmentioning
confidence: 99%
“…13 Several approaches have been studied such as adaptive artefact filters [18][19][20] or new SAAs designed to analyse either the artefacted 21,22 or the filtered ECG. 23 When tested on short strips (< 20 s) of OHCA data from defibrillators, only a recently published SAA 23 produced sensitivity and specificity results above 90% and 95%, the performance goals recommended by the American Heart Association (AHA). 24 Nevertheless, the reported sensitivities and specificities were well below those obtained for SAAs on artefactfree ECG.…”
Section: Introductionmentioning
confidence: 99%
“…Future developments should explore the design of CARFs for resuscitation rhythm annotation and the design of RCEs specifically for rhythm classification during CC-intervals, in line with some recent developments for shock advice algorithms. 25…”
Section: Performance For Rhythm Category Annotation On Complete Episodesmentioning
confidence: 99%
“…13 A study by Ruiz et al found that AFT reduces pauses in chest compressions during shockable arrest 14 and that the use of this particular AFT filter has reportedly high sensitivity (91.0%) and specificity (96.6%) for rhythm analysis during CPR in both shockable and non-shockable rhythms. 15 Despite the encouraging numbers, most manufacturers recommend a confirmatory pause prior to shock delivery. For this reason, we incorporated this pause into our study, but, as confidence in the technology increases, further gains may be made in improving CCF.…”
Section: Cjem Jcmumentioning
confidence: 99%